2022
DOI: 10.1136/bmjopen-2021-052481
|View full text |Cite
|
Sign up to set email alerts
|

Variation in on-scene time of emergency medical services and the extent of the difference of on-scene time between genders: a retrospective population-based registry study in Riyadh Province, Saudi Arabia

Abstract: ObjectivesTo identify the intergender variation of on-scene time (OST) for highly urgent emergency cases conveyed by emergency medical services (EMS) in Saudi Arabia and to assess other predictors of OST and hypothesise for possible factors delaying OST.DesignA retrospective population-based registry study.SettingRiyadh Province is the largest province in terms of population and the second in terms of geographical area.ParticipantsAll highly urgent transported patients from the scene to emergency departments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Older age is also known to be associated with longer on-scene time [3,22]. Age-related cognitive bias is one reason; another is failure of triage criteria to correctly identify elderly patients as they may sometimes appear to have less severe injury [23], even though this population can be severely injured from a less traumatic mechanism of injury [24].…”
Section: Discussionmentioning
confidence: 99%
“…Older age is also known to be associated with longer on-scene time [3,22]. Age-related cognitive bias is one reason; another is failure of triage criteria to correctly identify elderly patients as they may sometimes appear to have less severe injury [23], even though this population can be severely injured from a less traumatic mechanism of injury [24].…”
Section: Discussionmentioning
confidence: 99%
“…Older age is associated with prolonged OSTs in patients with trauma [ 14 ], those with road traffic injuries, highly-urgent transported patients [ 15 ], and transported patients [ 39 ]. Older people are likely to have more serious injuries than younger adults; thus, they may require a thorough assessment and a longer time for on-scene stabilization [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also revealed that the female sex was associated with prolonged OSTs. Females had longer median or average OSTs than males in urgent cases [ 15 ], trauma [ 7 ], and coronary artery syndrome [ 40 42 ]. However, the plausible reasons for the prolonged OST among female patients in these cases and those with minor diseases or injuries are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older age is also known to be associated with longer on-scene time [3,23]. Age-related cognitive bias is one reason; another is failure of triage criteria to correctly identify elderly patients as they may sometimes appear to have less severe injury [24], even though this population can be severely injured from a less traumatic mechanism of injury [25].…”
Section: Discussionmentioning
confidence: 99%